EVALUATING THE USEFULNESS OF THREE INDICES FOR ASSESSING WINTER TICK ABUNDANCE IN NORTHERN NEW HAMPSHIRE - Bergeron, Daniel H.; Pekins, Peter J. (Lakehead University, 2014)
In New Hampshire, winter ticks (Dermacentor albipictus) probably have more influence on the moose (Alces alces) population than other mortality factors, and predicting the frequency of tick epizootics is an important management consideration. Weather, moose density, and habitat use influence abundance and distribution of winter ticks. We evaluated the usefulness of 3 techniques to index winter tick abundance in 3 regions with variable moose density: 1) flagging for tick larvae, 2) line-transect counts of ticks on harvested moose, and 3) roadside surveys of tick-induced hairloss on moose. Although counts of tick larvae from fall flagging were not significantly different between years or regions, absolute tick abundance was measurably different (>50%) relative to moose density and years. Tick abundance on harvested moose reflected annual and regional differences; in general, abundance was correlated positively with moose density and annual trends within regions were similar. Tick abundance was highest for calves and lowest for cows. Hair-loss surveys indicated that hair loss was generally related to moose density, and similar annual differences were reflected in all regions. We suggest measuring tick abundance on harvested moose and conducting annual roadside hair-loss surveys to create indices and threshold values useful in predicting an epizootic of winter ticks.